Struggle of Hallucination As Seen in Beth Revis’ a World Without You - Yuli Astuti, Amelia; Haifa, Fadhilla (Fakultas Sastra Universitas Ekasakti, 2024)
The title of this research is “The Struggle Of Hallucination As Seen In Beth Revis’ A World Without You”. This thesis focuses on personality, external conflict, and hallucinations experienced by Bo as in the novel A World Without You. This research uses descriptive qualitative as a method in this final assignment, because the data are in the form of words and sentences written in the novel and analyzed descriptively. The data was obtained by the researcher by reading and writing sentences intensively and collecting several references from several books and dictionaries related to the subject matter and searching for information from the internet to support the research. The results of this study show the personality that occurs in Bo's life as a human being who has different personalities. External conflict occurs because Bo interacts with the people around him. Bo's hallucinations towards this make him and his family treated differently and it is difficult to accept the fact that his lover is no longer there.